EVALUASI KAPASITAS SALURAN DRAINASE DALAM MENAMPUNG LIMPASAN HUJAN DAN LIMBAH CAIR DOMESTIK DI Jl. SARIBU DOLOK SIMALUNGUN, INDONESIA - Daniel Mario Sidabutar; Rizky Simanjuntak; Rumila Harahap; Wisnu Prayogo (JURNAL SIMETRIK, 2026)
This study evaluates the capacity of drainage channels in accommodating stormwater runoff and domestic wastewater along Saribu Dolok Road, Simalungun Regency, Indonesia. Rapid population growth and escalating domestic activities in the area have led to increased volumes of wastewater and surface runoff, potentially exceeding the capacity of the existing drainage system. The objective of this research is to assess the adequacy of the current drainage infrastructure in handling projected hydrological loads. The methodology encompasses population projection analysis to estimate future domestic wastewater discharge, rainfall projection analysis to determine design rainfall intensities, and runoff discharge calculations employing standard hydrological methods. Furthermore, evapotranspiration analysis is conducted to refine water balance estimations, followed by hydraulic capacity assessment of the drainage channels and a comprehensive evaluation of the overall drainage system performance. The results reveal discrepancies between the existing channel capacities and the projected combined discharges from runoff and domestic wastewater, identifying segments that may underperform under peak conditions. These findings offer a technical foundation for pinpointing critical points in the drainage network and elucidating the interplay between hydrological inputs and channel performance under future scenarios. Keywords: Drainage Capacity, Runoff Discharge, Domestic Wastewater, Rainfall Projection, Evapotranspiration